2022
DOI: 10.1021/acsanm.2c00027
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Free-Standing Fe2O3 Nanoparticle/Carbon Shells/Graphene Films for Advanced Lithium-Ion Batteries

Abstract: High-capacity anode materials of transition-metal oxides (TMOs) usually undergo low conductivities and drastic volume variation derived from a multielectron-transfer conversion reaction mechanism, which seriously hinder the cycling stability and rate performance toward their commercialization. Herein, a free-standing Fe2O3/C shells/reduced graphene oxide (Fe2O3/C/RGO) film as an additive-free anode is fabricated by a facile two-step strategy accompanied by the physical cross-linking feature of chitosan. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The Fe 3+ ions were then well adsorbed on the surface of GO sheets with abundant oxygenic functional groups via the electrostatic adsorption effect, which on the surface of GO sheets (Figure 2a). 25 Subsequently, a 3D RGO aerogel scaffold was prepared by a sample freeze drying 26 As shown in Figure 2f, the corresponding SAED pattern reveals the crystal symmetry, which is well-consistent with the XRD results. 27 28 No other phases or impurities are detected, indicating a high purity of FeF 3 •0.33H 2 O under such synthetic conditions.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The Fe 3+ ions were then well adsorbed on the surface of GO sheets with abundant oxygenic functional groups via the electrostatic adsorption effect, which on the surface of GO sheets (Figure 2a). 25 Subsequently, a 3D RGO aerogel scaffold was prepared by a sample freeze drying 26 As shown in Figure 2f, the corresponding SAED pattern reveals the crystal symmetry, which is well-consistent with the XRD results. 27 28 No other phases or impurities are detected, indicating a high purity of FeF 3 •0.33H 2 O under such synthetic conditions.…”
Section: Resultssupporting
confidence: 71%
“…XRD patterns of the Fe 2 O 3 /RGO-2 precursor, unsupported FeF 3 ·0.33H 2 O, and FeF 3 ·0.33H 2 O/RGO nanocomposites are shown in Figures a and S3, where the Fe 2 O 3 /RGO-2 precursor was identified as γ-Fe 2 O 3 (JCPDS #39-1346) . After the evolution process, FeF 3 ·0.33H 2 O/RGO-1.5, FeF 3 ·0.33H 2 O/RGO-2, FeF 3 ·0.33H 2 O/RGO-5, and unsupported FeF 3 ·0.33H 2 O show the same well-defined characteristic peaks at 13.8, 23.4, 27.5, 27.8, and 34.0° assigned to the (110), (002), (022), (220), and (132) lattice planes of hexagonal tungsten bronze-type FeF 3 ·0.33H 2 O (JCPDS #76-1262), respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal disulfides such as WS 2 [97,98] , SnS 2 [99] , TiS 2 [100,101] , VS 2 [102] have similar layered structures to MoS 2 . The metal atomic layer is sandwiched by the S atomic layer; The large specific surface area and sulfophilic properties adsorb more polysulfides; The intercalation/deintercalation mechanism is conducive to the conduction of electrons.…”
Section: Separator Modificationmentioning
confidence: 99%
“…For instance, our group recently proposed a facile freeze-drying selfassemble strategy to prepare a free-standing Fe 2 O 3 /rGO film, which exhibited a superior electrochemical performance for anode. 28 Also, Zhang et al reported ultrafine Fe 2 O 3 nanorods anchored on GO by a one-pot route in the presence of KMnO 4 and Ni foam, and showed an outstanding cycling stability (a reversible capacity of 1004 mAh g −1 after 500 cycles at 0.2 A g −1 ). 29 Consequently, the combination of nano-crystallization and composed with flexible graphene is expected to improve the lithium storage performance through "synergistic effect," which is of great significance to probe the structure-performance relationship for the development of highperformance TMOs-based anode materials for LIBs.…”
mentioning
confidence: 99%